Le massif de Lovo, sur les traces du royaume de Kongo. - Heimlich, Geoffroy, (Cambridge monographs in African archaeology ;, 2017)
Unlike the Sahara or Southern Africa, the rock art of Central Africa is still largely unknown today. Crossing ethnological, historical, archaeological and mythological points of view, this book illustrates that rock art played an important part in Kongo culture.